Estimacion de varianzas geneticas en maiz a partir de lineas S1 y S2 - Navarro, F.V.=700 1 Youngquist, W.C.; Compton, W.
(En, Es)
ilus., 15 ref.
Keywords: ZEA MAYS; FITOMEJORAMIENTO; VARIACION GENETICA; HIBRIDACION; COSTA RICA